(untitled) (Fiep Bulletin - online, 2015)
The general theme of the III Luso-Brazilian Congress of Physical Education "People’s physical education according to their degree of evolution”, is extremely interesting and also very difficult to treat, at least for the author of this essay. I shall therefore limit myself to the study of some aspects of its aspects.